The Effects of Professional Development in Formative Assessment on Mathematics Teaching Performance and Student Achievement - Maggie B. McGatha; William S. Bush; Christopher Rakes (The Evaluation Center at Western Michigan University, 2009)
This article describes a year-long professional development program on formative assessment for middle school mathematics teachers and its impact on teachers' use of formative assessment during instruction. The focus of the program was to support teachers in (a) embedding formative assessments into their instruction, (b) interpreting student responses and performance on formative assessments, (c) using effective questioning strategies and peer assessment, and (d) identifying student errors and misconceptions and implementing instructional strategies to address them. Teacher and student performance data were collected on participating teachers, control teachers, and their students during the year-long professional development. The professional development had an impact on teachers' cognitive level of questioning, use of peer assessment, and types of questioning strategies. Results of student performance data revealed differences in performance on some types of items among students of participating teachers and control teachers.